Applying Problem-Based Learning in Management Schools - Hryniewicz, Lygia; Bayma de Oliveira, Fatima; de Souza Sant'Anna, Anderson; Camisão Loyola, Breno (Revista Educação e Cultura Contemporânea, 2024)
The aim of this article is to discuss the potential of new pedagogical methodologies for enhancing management skills in management schools, as a complement to the traditional method. In this study, we adopted a bibliographic method to explore the concept, characteristics, and use of Problem-Based Learning teaching methodologies (PBL) in higher education courses, particularly in management schools. Moreover, we used a narrative research method, which included interviewing a Brazilian Professor with experience in implementing PBL teaching in a higher education institution. Our study also describes a practical application of PBL at the Fundação Getúlio Vargas. The results showed that different methods reflect different multidimensional learning processes, whether intentional or not. In a constantly changing society, everything we share cognitively or emotionally becomes more complicated, as many of the values taught and learned do not correspond to the real world. We emphasize that the traditional education method still holds a significant place in higher education courses due to its institutional importance, numerous certifications, and the investments made over the years.